Analysis of Inflation, Money Supply, Total Credit and Poverty Effect on Gross Regional Domestic Product of North Sulawesi Province - Juan Wokas; Paulus Adrian Pangemanan; Grace Adonia Josefina Rumagit (Universitas Sam Ratulangi, 2023)
This research aims to analyze the effect of inflation, money supply, total credit and the poverty rate on the Gross Domestic Regional Product (GRDP) of North Sulawesi Province, and predict the conditions for the next 5 years of the variables that will most dominantly affect GRDP of North Sulawesi Province. The data used in this research are secondary data obtained from the Central Bureau of Statistics of North Sulawesi Province and online publications of Bank Indonesia. The analysis used in this research are multiple linear regression analysis and the Autoregressive Integrated Moving Average (ARIMA) method. The results of this research show that inflation, money supply, total credit, and poverty simultaneously affect the GRDP of North Sulawesi Province. Partially, the inflation and poverty variables have a significant negative effect on GRDP, while the money supply and total credit variables have a significant positive effect on GRDP. The most dominant variables affecting regional gross domestic product are the money supply and total credit. Forecasting results show that the money supply for the next 5 years has a trend that tends to show a fluctuating increase and total credit also shows an increasing condition from year to year for the next 5 year period.